Analysis Of The Needs For A Project-Based Learning (PJBL) Model With Aswaja Characteristics In Mathematics Courses For Elementary School Teacher Education Students - Nurdiansyah, Erwin; Arismunandar, Arismunandar; Upu, Hamzah (Journal of Research and Multidisciplinary, 2025)
The needs analysis for implementing Project-Based Learning (PBL) with Aswaja values in mathematics courses at the Primary School Teacher Education (PGSD) Program is essential to assess student and lecturer readiness, challenges, and preferences. This study aims to analyze the need for a PBL model with Aswaja values to enhance students' mathematics learning outcomes at the Islamic University of Makassar. Using a qualitative descriptive approach, the study explores the application of this model in PGSD mathematics courses. Data were collected from students and lecturers through observation, documentation, and questionnaires, then analyzed using qualitative techniques, including coding, analysis, data triangulation, and presentation. The findings indicate a strong need for a PBL model with Aswaja values, as seen in three key aspects: learning model needs, learning challenges, and learning expectations. This study contributes to integrating PBL with Aswaja values systematically, enhancing both mathematical understanding and character development in PGSD students.